(untitled) (Bangladesh Journal of Medical Science, 2016)
Retropharyngeal abscess (RPA) is defined as a potentially serious deep neck space infection, commonly seen in children and usually associated with prior upper respiratory tract infection (URTI), history of trauma or foreign body ingestion. We report a rare case of RPA and longus capitis intramuscular abscesses in a 4 year old, who presented with chief complaint of torticollis but with normal oropharyngeal findings. RPA, longus capitis inflammation may be common but abscess in the longus capitis muscle is rare. The aim of this case report is to highlight that subclinical RPA in pediatric age group may present with only acquired torticollis and without sore throat nor high fever. Diagnosis and evaluation of extension was made with contrast enhanced computer tomography (CECT) of the neck. In stable patient with non-extensive abscess and low risk of developing complications, medical management is always the preferred choice. Bangladesh Journal of Medical Science Vol.15(4) 2016 p.645-647